Pandangan Praktis Realis dan Pandangan Idealis Tentang Keuntungan dan Pelayanan dalam Kewirausahaan - Aris Sampe (Riviera Publishing, 2026)
Entrepreneurship is not solely associated with profit generation but also with the noble value of serving customers and society. In practice, two dominant perspectives often shape entrepreneurial decision-making: the practical-realistic perspective and the idealistic perspective. This study aims to analyze both perspectives in the context of entrepreneurship and identify their implications for profit orientation and service quality. The research applied a qualitative literature review with a comparative approach to national and international publications on business ethics, entrepreneurial practices, and decision-making paradigms. The findings reveal that the practical-realistic perspective positions profit as the main objective, in which service is treated as a business strategy, whereas the idealistic perspective views service as a moral calling where profit becomes a long-term outcome of customer satisfaction. The synergy of both perspectives forms the most effective entrepreneurial model in the current competitive era, leading to sustainable business growth based on balanced profit and service values. This research also identifies that implementing a hybrid model integrating both paradigms can simultaneously enhance competitiveness, business sustainability, and corporate social contribution.